Mengintegrasikan Pendekatan Teaching at the Right Level (TaRL) dan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Motivasi Belajar Peserta Didik. - Fardin, Fardin; Sofyan, Muhamad; Khandra Mulia, Baiq (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
The Teaching at the Right Level (TaRL) approach aims to group students according to their ability levels to enhance learning effectiveness. Meanwhile, Problem-Based Learning (PBL) emphasizes students’ active engagement in solving problems that are relevant to their real-life contexts. This study seeks to integrate these two approaches to improve students’ learning motivation. A mixed-methods design was employed, combining qualitative and quantitative approaches to obtain comprehensive data. The findings indicate that the integration of TaRL and PBL significantly enhances students’ learning motivation, particularly in the aspects of active participation, perseverance, and learning autonomy. Therefore, the integration of these approaches can serve as an effective instructional strategy to promote a more inclusive and needs-based educational environment.